2020
DOI: 10.3892/ijo.2020.5134
|View full text |Cite
|
Sign up to set email alerts
|

Glioma cells are resistant to inflammation‑induced alterations of mitochondrial dynamics

Abstract: Accumulating evidence suggests that inflammation is present in solid tumors. However, it is poorly understood whether inflammation exists in glioma and how it affects the metabolic signature of glioma. By analyzing immunohistochemical data and gene expression data downloaded from bioinformatic datasets, the present study revealed an accumulation of inflammatory cells in glioma, activation of microglia, upregulation of proinflammatory factors (including IL-6, IL-8, hypoxia-inducible factor-1α, STAT3, NF-κB1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…β2 microglobulin and cytochrome C oxidase subunit 6B1 showed a similar trend and significantly higher levels of m-GBM, again confirming differences between male and female GBM profiles. These results are in accordance with the reported overexpression of cytochrome C oxidase subunit 6B1 in gliomas, which accomplishes mitochondrial metabolic remodeling in this disease, and it is involved in apoptosis inhibition, mitochondrial function modulation, and stress resistance [ 22 ].…”
Section: Resultssupporting
confidence: 91%
“…β2 microglobulin and cytochrome C oxidase subunit 6B1 showed a similar trend and significantly higher levels of m-GBM, again confirming differences between male and female GBM profiles. These results are in accordance with the reported overexpression of cytochrome C oxidase subunit 6B1 in gliomas, which accomplishes mitochondrial metabolic remodeling in this disease, and it is involved in apoptosis inhibition, mitochondrial function modulation, and stress resistance [ 22 ].…”
Section: Resultssupporting
confidence: 91%
“…The analysis revealed that T98G cells showed increased basal levels of ROS, which did not change after menadione treatment, whereas HepG2 cells responded to the treatment and OS was induced (Figure 1C). This might indicate that the redox state of GBM cells protects them from apoptosis, thus creating a favorable environment for cellular proliferation and inducing drug resistance [10,57].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is known to foster an inflammatory immune response that could shift the tumor microenvironment into a pro-tumorigenic milieu ( Fan et al, 2020 ). Acute and transient inflammation may inhibit tumor growth ( Fan et al, 2020 ) by upregulating pro-inflammatory cytokines such as TNFα, IL-1β, and IL-6 that are part of the initial inflammatory cascade and recruit other downstream targets to enhance anti-tumor responses. However, if inflammation becomes a chronic occurrence, the same inflammatory processes can exhaust the immune system’s ability to fend off glioma cells.…”
Section: Inflammation In Gliomamentioning
confidence: 99%